2013
DOI: 10.1111/pcn.12127
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter population‐based study on the prevalence of early onset dementia in Japan: Vascular dementia as its prominent cause

Abstract: Aim:In Japan, the government and media have become aware of the issues of early onset dementia (EOD), but policies for EOD have not yet been established and support systems are inadequate. To provide practical data about EOD, a two-step postal survey was performed.Methods: A questionnaire requesting information on EOD cases was sent to target institutions in five catchment areas in Japan. According to the answers from the institutions, we estimated the prevalence of EOD using census data and determined the ill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(28 citation statements)
references
References 19 publications
1
23
1
3
Order By: Relevance
“…All underwent structural neuroimaging with magnetic resonance imaging of the brain and routine laboratory tests. In addition to these 63 hospital outpatients, we included 29 EOAD patients from our community‐based survey on the prevalence of early onset dementia . This study was conducted in the same catchment area as our university hospital in 2008.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…All underwent structural neuroimaging with magnetic resonance imaging of the brain and routine laboratory tests. In addition to these 63 hospital outpatients, we included 29 EOAD patients from our community‐based survey on the prevalence of early onset dementia . This study was conducted in the same catchment area as our university hospital in 2008.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to these 63 hospital outpatients, we included 29 EOAD patients from our community-based survey on the prevalence of early onset dementia. 21 This study was conducted in the same catchment area as our university hospital in 2008. We visited these EOAD patients at home, in the hospital, or in the nursing home and examined them using the same procedure as used on the outpatients.…”
Section: Subjectsmentioning
confidence: 99%
“…EOD results in severe impact on employment, social functioning, financial status and family relationships, thereby reducing patient quality of life. Alzheimer's disease (AD) and vascular dementia are the most common causes of EOD . In our previous study involving patients with AD, it was revealed that the proportion of patients with early‐onset AD was approximately 3% amongst all patients in the study population .…”
Section: Introductionmentioning
confidence: 97%
“…Dementia affects 47.5 million people worldwide, with 7.7 million new cases emerging each year . The prevalence of dementia in patients aged <65 years, typically defined as early‐onset dementia (EOD), has recently been reported as between 48 and 172 per 100 000 individuals . EOD results in severe impact on employment, social functioning, financial status and family relationships, thereby reducing patient quality of life.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation